GAMBARAN PRAKTIK PERSONAL HYGIENE PADA LANSIA DI PANTI SOSIAL LANJUT USIA TRESNA WERDHA KOTA SEMARANG - Annisa Trisnani; Besar Tirto Husodo; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The elderly population continues to grow every year due to poor health status. One of the efforts to maintain the health of the elderly with preventive measures is by doing personal hygine. Hygine personal practices can be directed to maintain in order to stay healthy and productive life socially and economically in accordance with human dignity. The maintenance of personal hygiene includes the cleanliness of hair, eyes, ears, teeth, mouth, skin, nails, and hygiene in the dressing. To be able to perform personal hygiene of the elderly requires a good knowledge that can be applied to personal hygiene as possible. This study aims to describe the practice of personal hygiene of the elderly in the Elderly Social Panti Tresna Werdha Semarang. This type of research is descriptive analysis method with quantitative techniques using cross-sectional study. The population is all inhabitants of the Institution. Total sample of 33 elderly respondents with a total sampling techniques in accordance with the criteria specified. Sources of data research using primary and secondary data. Data analysis using univariate analysis results showed the beginning of elderly respondents (75.8%) of the women (57.6%) had not completed school seniors (45.5%) practices of the elderly (57.6%), knowledge (42.4%) , attitude (48.5%) were not available infrastructure (69.7%) affordability facilities are not affordable (69.7%) are less supportive role officers (69.7%) support the role of less friends (90.9%).